Relationship between nurses' perception of professional shared governance and their career motivation: A cross-sectional study - Amal Diab Ghanem Atalla; Loujain Saud Sharif; Nouran Essam Katooa; Faten Shawky Kandil; Alaa Mahsoon; Naglaa Abdelaziz Mahmoud Elseesy (Elsevier, 2023)
Objectives: This study aimed to investigate the level of professional shared governance and career motivation and their relationship among nurses in Egypt. Methods: A cross-sectional survey was conducted. A total of 724 nurses working in inpatient medical, surgical, and critical care units in Alexandria Main University Hospital were recruited from May to August 2022. The Index of Professional Nursing Governance (IPNG) version 3.0 and the Career Motivation Scale were used for evaluation. Results: The IPNG version 3.0 total score was 109.18 ± 22.76, that nurses perceived had a low level of professional shared governance; the access to information dimension achieved the highest average mean score (2.81 ± 0.76), followed by the ability to set goals and conflict resolution dimension (2.75 ± 0.53). On the other hand, the dimension of participation in the committee structure achieved the lowest average mean score (1.65 ± 0.37). The total score of career motivation was 69.82 ± 9.70 this reflects that nurses perceived a moderate level of career motivation. The career insight dimension achieved the highest average mean score (3.56 ± 0.34), while the career resilience dimension achieved the lowest average mean score (3.07 ± 0.49). Male nurses, less than 30 years old, had a bachelor's degree in nursing sciences, and worked in the ICU had higher total scores of the IPNG and career motivation (P < 0.001). There was a positive correlation between the IPNG version 3.0 score and the Career Motivation Scale score (r = 0.239, P = 0.003). Conclusions: The study's findings can serve as a theoretical foundation for nursing managers to re-plan the management model and develop appropriate methods to give better career planning for nurses.